Dinamika Regulasi Wakaf di Indonesia dalam Konfigurasi Politik - Solikhul Hadi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
The long process of regulation of Islamic law - especially the law of waqf - is always interesting to observe or study, because its presence cannot be separated from the things that underlie it. This study aims to examine the effect of Indonesia's political configuration on the character of waqf regulatory products in Indonesia. By using qualitative methods, it is hoped that this study will be able to describe the character of products of waqf regulation which are influenced by political configurations from the New Order Era to the Reformation Era with a historical approach. The results of this study indicate that the character of waqf regulations in Indonesia varies according to the political configuration that surrounds them. There are at least three important periods that show the dynamics of political configuration that affect the character of waqf regulation. First the Old Order Period, Law no. 5 of 1960 (UUPA), which also regulates waqf and land issues, is responsive in character. Secondly, during the New Order era, the regulations governing waqf during the New Order era were conservative / orthodox in character. The regulation that regulates waqf during the New Order era is PP. 28 of 1977 concerning Ownership of Land Owned, Law no. 7 of 1989 concerning Religious Courts (Chapter III), and Compilation of Islamic Law based on Presidential Instruction No.1 of 1991. In Chapter III. And there are also several regulations issued by the Minister and Director General level. And thirdly the Reformation Period, the Law that regulates waqf Law no. 41 of 2004 has a democratic character.AbstrakProses panjang regulasi hukum Islam utamanya hukum wakaf selalu menarik untuk diamati atau diteliti, karena kehadirannya tak lepas dari hal-hal yang melatarbelakanginya. Studi ini bertujuan untuk meneliti pengaruh konfigurasi politik Indonesia terhadap karakter produk regulasi wakaf di Indonesia. Dengan menggunakan metode kualitatif diharapkan studi ini akan bisa mendeskripsikan karakter produk regulasi wakaf yang dipengaruhi oleh konfigurasi politik mulai Era Orde Baru sampai dengan Era Reformasi dengan pendekatan historis. Hasil penelitian ini menunjukkan bahwa karakter regulasi wakaf di Indonesia berbeda-beda sesuai dengan konfigurasi politik yang melingkupinya. Setidaknya ada tiga periode penting yang menunjukkan dinamika konfigurasi politik yang mempengaruhi karakter regulasi wakaf. Pertama Masa Orde Lama, Undang-Undang Nomor 5 Tahun 1960 (UUPA) yang di dalamnya juga mengatur tentang wakaf dan permasalahan pertanahan adalah berkarakter  responsif. Kedua Masa Orde Baru, regulasi  yang mengatur tentang wakaf pada masa Orde Baru berkarakter konservatif/ortodoks. Regulasi  yang mengatur tentang wakaf pada masa Orde Baru adalah Peraturan Pemerintah Nomor 28 Tahun 1977 tentang Perwakafan Tanah Milik, Undang-Undang Nomor 7 Tahun 1989 tentang Peradilan Agama (Bab III), dan Kompilasi Hukum Islam berdasarkan Inpres No.1 Tahun 1991. Pada Bab III dan juga ada beberapa peraturan yang dikeluarkan oleh setingkat Menteri dan Dirjen. Dan ketiga  Masa Reformasi, Undang-Undang yang mengatur tentang wakaf Undang-Undang Nomor Nomor 41 Tahun 2004 berkarakter demokratis.